Report of the National Executive Committee to the 39th annual conference to be held in The Pavilion, Bournemouth, May 13th - 16th, 1940. - Labour Party (London : Labour Party, 1940)
Bibliotheek Camille Huysmans
Engels
Monografie
Keywords: Labour Party; Wereldoorlog 2; Groot-Brittannië.